Explainer montage video as an effective tool for development plan presentation: a case study of Manjung Smart City Action Plan, Perak, Malaysia / Che Ahmad Rahiman Che Rozaid ... [et al.] - Che Rozaid, Che Ahmad Rahiman; Hasnizam, Hadif Azwar; Shamsuddin, Muhamad Syafiq; Abdul Rashid, Mohd Fadzil; Boon Lim, Seng (2024)
Modernisation nowadays, worldwide and in Malaysia, where video technology has advanced, montage techniques have become more accessible and widely adopted. Montage Video is applied in various fields, including marketing and advertising, music video, social media content, explainer videos, documentary filmmaking and personal storytelling. Especially the explainer montage video can effectively explain complex ideas, processes, or data by breaking them down into a series of visually compelling, easily digestible segments. This technique is widely used in educational, instructional, and corporate explainer videos. However, the current innovation lacks a detailed exploration of how explainer montage videos can enhance the visual presentation of new ideas in an (participatory) urban planning development plan presentation. This research project aims to innovate how explainer montage video can enhance the visual presentation of new ideas in urban and regional planning contexts, especially for development plan projects. The Manjung Smart City Action Plan, Perak real project, has been selected as the case study. Through this project design and application, the professional software Adobe Premiere Pro, Adobe After Effects and Google Earth Studio for video editing were adopted. New and innovative presenting effects, such as a specialised interface for 3D Earth animations, advanced motion graphics, and VFX, are being explored in this project. This research project has contributed to an innovative and creative idea for a montage video that revitalises the mode of typical amateur mobile video editing/ presentation tools, i.e., CAPCUT and VN, especially for pitching sessions for development plan projects in local authorities and government agencies.